The Effect of Tam Factor on Repurchase Intention in E-Satisfaction Mediation on the Millenial Generation: Study on Go-Pay E-Wallet - Nuri Herachwati; Zuyyinah Choirunisa; Provitadiaz Wibowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Every firm in technology industy needs to adapt in the current business environtment so they can adapt and survive in the midst of intense competition. Technology Aceptance Model (TAM) is one of the tools that can be used to penetrate the current business environtment. The purpose of this study is to analyse the effect of TAM factor on repurchase intentention using e-satisfaction as mediating effect. The variable used in this study are security, ease of use, privacy concern, e-satisfaction, repurchase intention. This research use quantitative method using quesionaaires. The population used in this study are millennial generation in the city Surabaya who used e-wallet Gopay. The sampling technique in this research is using non probability sampling and consisted of 385 people. Data were analyse using SEM-PLS method. From the result of the study concluded that among all variable were found to have positive and significant effect towards repurchase intention exlude the variable of privacy concern.